Planning the Urban Food System of the Metropolitan Área of Lisbon. A conceptual framework - Oliveira, Rosário (2016)
The current global crisis and the acknowledgment that in coming decades the world population will be predominantly urban brings about new necessities and demands for innovative approaches to the planning of food systems. An urgent need arises to identify the most efficient and consistent ways of dealing with problems concerning economic and energy efficiency, environmental quality, food security, job creation, and urban development. In the past few years, international political and scientific agendas and strategies for food security in metropolitan areas highlight the need to relocalize production–consumption systems through shorter, more efficient supply chains, as a means of promoting sustainable urban development via place-based approaches. The provision of efficient responses to environmental, economic, and social concerns, emerging in a context of complex global change, needs to be tackled at a local and regional level. The study of urban food systems becomes fundamental for an integrated approach to these internationally set priorities. However, this issue has yet to enter on either of the Portuguese political or academic agendas. In Portugal, the structural changes that occurred in the food system in the last decades reflect an increased socioeconomic impoverishment of the countryside vis-à-vis urban areas. Consequently, there are deeper inequalities in terms of territorial cohesion. Moreover, in the Lisbon Metropolitan Area (LMA), where a third of the Portuguese population lives, utilized agricultural area represents 37 percent of the territory, a figure which by itself justifies the need to adopt a strategic vision for the LMA’s food system planning. This paper will give insight into the conceptual definition of the functional region as the area where the LMA’s food system might operate, providing orientation to land-use management and strategic planning that should be able to promote the re-localization of the food system in a sustainable way. The characterization of the current LMA food system is seen as a starting point for understanding how to develop a resilient urban food system based on adequate spatial planning concepts and tools. This paper seeks to discuss a feasible conceptual framework for the design of a sustainable solution to feed the Lisbon metropolis, while simultaneously promoting its economic vitality, environmental quality, spatial justice, and cultural identity.